2010
DOI: 10.1017/s0714980810000589
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation des aînés à la résidence pour personnes âgées: Activité de loisirs et autodétermination

Abstract: The purpose of this study was to better understand adjustment and life satisfaction in later life. In particular, it examined the contribution of leisure participation and motivation toward leisure in older people's adjustment to their nursing homes and their satisfaction with life.. Study results underlined the contribution of participation in leisure activities both to the adaptation of an elderly person to his residence and to life satisfaction. In terms of adaptation to the residence, participation in recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
2
13
0
3
Order By: Relevance
“…Notably, the engagement in leisure (measured by the frequency and the number of activities) is positively correlated with the satisfaction with life as well as to the two forms of self-determined motivations (IM and self-determined EM). The relationship between participation in leisure activities and self-determined motivation was reported in past research (Altintas et al, 2010;Coleman & Iso-Ahola, 1993;Iso-Ahola, 1999;Losier et al, 1993;Vallerand & O'Connor, 1991). However, this research extends those findings by showing a relationship for older persons between engagement in leisure activities, self-determined behaviours towards daily activities, and both psychological and environmental adjustment to the nursing home.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, the engagement in leisure (measured by the frequency and the number of activities) is positively correlated with the satisfaction with life as well as to the two forms of self-determined motivations (IM and self-determined EM). The relationship between participation in leisure activities and self-determined motivation was reported in past research (Altintas et al, 2010;Coleman & Iso-Ahola, 1993;Iso-Ahola, 1999;Losier et al, 1993;Vallerand & O'Connor, 1991). However, this research extends those findings by showing a relationship for older persons between engagement in leisure activities, self-determined behaviours towards daily activities, and both psychological and environmental adjustment to the nursing home.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, other studies reported that there was no significant correlation with life satisfaction (Altintas et al, ; Solberg et al, ) or with depression (Altintas & Guerrien, ).…”
Section: Resultsmentioning
confidence: 82%
“…Autonomous motivation was positively associated with adaptation of the elderly to the nursing home (Altintas et al, , ) and with vitality (Solberg et al, ) but was negatively associated with depression (Altintas & Guerrien, ) and negative affect (Sheldon & Kasser, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations